Predatory fishing monitoring with the use of geographic information system (Research, Society and Development, 2020)
The Brazilian Institute of Environment and Renewable Natural Resources (IBAMA) determines a regulatory set of instructions for fisheries agreements. These rules control fishing activity in Brazilian basins during closed fishing seasons. However, many fishermen violate the agreements, as seen in the river basin Uba, in the municipality of Moju-Pará. When fishermen breach IBAMA’s stated regulations, the municipality is urged to act on the case, but with little knowledge of critical areas which suffer from overfishing. This makes the logistics of solving these issues difficult and often problematic. This work strives to serve as an aid to environmental agencies in their endeavor to inspect and regulate the issue of overfishing in critical areas, such as the Úba river basin in the municipality of Moju-Para. Our methods include a literature review of research concerning the issue, identifying critical points, as well as preparing maps and proposals for the site of environmental monitoring activities in the city. From within the critical points, we identified the hot spots. We observed five distinct vegetation types located roughly 10 kilometers along the river, and the corresponding agricultural anthropic areas to 49% of the entire study area’s territory. It is noted that the areas of greatest concentrations of overfished territories are lined with countryside, forest and dense vegetation. Thus, environmental inspections should take place in areas near the communities and the Úba river and especially in the area beyond the Levi resort, where the hot spot was identified, while always considering the logistics for hard to reach areas.